The Impact Of Agricultural Extension Contact On Crop Income In Bangladesh (Bangladesh Journal of Agricultural Research, 2013)
The impact of extension contact on crop income is examined with a view to evaluating the agricultural extension in Bangladesh. The scope of the study was ten villages of Gazipur district. The objectives of the study are to i) determine the factors influencing the benefit of extension services in terms of farm income, ii) determine the factors affecting the extension contact of farmers, and iii) suggest some policy guidelines to improve the extension services in Bangladesh. The sample of the study consists of 1000 farmers. Data came from field survey and multistage random sampling technique was used in order to collect data. The results indicated that the impact of extension contact coefficient on crop income is positive and significant. Evidence shows that the influence of extension contact coefficient is strongly positive and significant in the comparatively nearer villages to upazila headquarters, while this effect is weaker for those villages, which are comparatively away from upazila headquarters. It is found that many farmers did not receive extension contact and the effect of extension contact is weak on crop income compared to other factors such as irrigation and chemical fertilizer. It is assumed that there was enough scope to increase extension contact in the study areas. Some determinants of extension contact were also examined. The study concludes that agricultural extension is necessary to increase among the farmers. Bangladesh J. Agril. Res. 38(2): 321-334, June 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i2.15893